2019
DOI: 10.21315/mjms2019.26.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Factors Influencing Time of Arrival at Emergency Departments for Patients with Acute ST-Elevation Myocardial Infarction

Abstract: BackgroundPre-hospital delay is currently a major factor limiting early reperfusion among ST-elevation myocardial infarction (STEMI) patients worldwide. This study aims to determine pre-hospital factors affecting symptom-to-door time among STEMI patients in Malaysia.MethodsThis cross-sectional study included 222 STEMI patients admitted to two tertiary hospitals in Malaysia. By determining symptom-to-door time, the study population was categorised into two definitive treatment seeking groups: early (≤ 3 h) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
0
21
2
Order By: Relevance
“…26,27 The mean age of the participants in this study was similar to that in a study in Malaysia. 28 Previous studies found that females were more likely to arrive late compared with males, but our findings failed to find statistically significant differences between males and females. 16,29,30 In the current study, bivariate analysis showed that current smokers were less likely to arrive late, and current smokers might perceived high susceptibility to Values are presented as numbers and percentages (%).…”
contrasting
confidence: 90%
See 2 more Smart Citations
“…26,27 The mean age of the participants in this study was similar to that in a study in Malaysia. 28 Previous studies found that females were more likely to arrive late compared with males, but our findings failed to find statistically significant differences between males and females. 16,29,30 In the current study, bivariate analysis showed that current smokers were less likely to arrive late, and current smokers might perceived high susceptibility to Values are presented as numbers and percentages (%).…”
contrasting
confidence: 90%
“… 7 Other previous studies found that patients who had history of hypercholesteremia were less likely to arrive late to the hospital. 28 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of studies, male gender and younger age were associated with earlier treatment of ACS compared to females and older adults, respectively [19] , [23] , [31] , [33] , [34] , [35] . Several studies reported however, that there were no differences in treatment for ACS due to either gender or age characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The overall in-hospital mortality rate was 19.51%, MACE at 30 days, 23.17% (38/164), respectively. ** * * Fair Lim et al, 2019 [35] Cross-sectional, descriptive. 2 tertiary care hospitals in Malaysia 222 Mean age 58 ± 11.9 years.…”
Section: Methodsmentioning
confidence: 99%